Lathyrane diterpenoids from Jatropha podagrica and their antitumor activities in human osteosarcoma cells. Issue 23 (2nd December 2021) - Yuan, Han-Tao; Li, Qun-Feng; Tian, Tian; Zhang, Chun-Yan; Huang, Zou-Qin; Fan, Chun-Xiang; Mei, Ke; Zhou, Jie; Zhai, Xiao-Xiang; Li, Si-Bo; Zhu, Jian-Yong
Abstract: Two new lathyrane-type diterpenoids, jatropodagins A and B (1 and 2 ), and five known analogues (3 –7 ), were isolated from the stems of Jatropha podagrica . Their structures and absolute configurations were elucidated by spectroscopic data and calculated ECD analyses. The cytotoxicities of all the lathyrane-type diterpenoids (1 –7 ) were evaluated against two human osteosarcoma cell lines (Saos-2 and MG-63). Compound 1 exhibited significant cytotoxic effects against Saos-2 and MG-63 with IC50 values of 8.08 and 14.64 μ M, respectively. The IC50 values for the positive control 5-FU against the Saos-2 and MG-63 cell lines were 19.01 and 25.00 μ M, respectively. Morphological features of apoptosis activities were evaluated in 1 -treated Saos-2 cells and the results confirmed apoptosis in a dose-dependent manner. Graphical Abstract: